Great events - "Tames, Richard" (London; Watts Books, London, 1995)
Tells the stories of some major historical events, including the American War of Independence, the Russian Revolution and Pearl Harbor, and invites the reader to decide what happened next by choosing from a variety of alternatives. Suggested level: junior secondary
Keywords: Military history,-Book